Primary de novo intraosseous carcinoma of the mandible: A rare case report - Kotya Naik Maloth; Vinay Kumar Reddy Kundoor; Srikanth kodangal; Nagajyothi Meka (Wolters Kluwer Medknow Publications, 2014)
Primary intraosseous carcinoma (PIOC) is a very rare, but well-recognized entity, which is locally aggressive with quite poor prognosis. It may arise within the jaws either from a previous odontogenic cyst or de novo, rather than from a pre-existing epithelial lesion. A case of PIOC arising in the mandible of a 63-year-old male patient is reported in this article, with the clinical, radiological, and histological features described. This rare lesion must be considered in any differential diagnosis of jaw radiolucency.